Impact of Jharkhand Department of Agriculture on Knowledge, Attitude and Adoption of the Farmers - Choudhary, Jatashankar; Jha, B.K.; Sarkar, P.K.; Ratan, R.P. Singh (Indian Journal of Extension Education, 2017)
The responsibility of transfer of technology lies with the State Department of Agriculture which undertakes a number of activities aiming at changing the behavior of the farmers. In recent past, there have been a lot of questions on the performance of Department of Agriculture. In this backdrop, a study was conducted to assess the impact of Jharkhand Department of Agriculture on the farmers. One district each from the five divisions of the state was randomly selected. Similarly, two blocks from each district were selected randomly. Twenty participant farmers and twenty non-participant farmers were selected randomly from each block making the sample size of 400 farmer respondents. The findings revealed that the participant farmers had higher mean values in knowledge, attitude and adoption and differed significantly from non-participant farmers. The variable extension contact had contributed significantly towards variability in knowledge, attitude and adoption. It could be concluded that the efforts of Jharkhand Department of Agriculture has yielded results which is reflected in the behavior of participant farmers.
Keywords: Impact; Knowledge; Attitude; Adoption; Agriculture